Pengaruh Faktor Keuangan Pemerintah Daerah terhadap Kualitas Internet Financial Reporting - Diptyana, Pepie (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. Internet financial reporting (IFR) promotes transparency to maintain government-citizen relationship. Prior research has indicated that transparency in government depends on institutional and environmental factors. Nevertheless, those research shown heterogeneity results, so then academic researchers have difficulties to find out consistent conclusion. This research aims to identify financial factors which support local government IFR quality. We use 91 local governments in Indonesia as samples. Data was analyzed by multi regression and 5% significant level. Five independent variable were tested: liquidity, leverage, service level solvency (SLS) based on expenditure, SLS based on asset value, and financial dependence. Result shows that service level solvency as representation of local government ability to serve its citizen is significant to IFR quality. Keywords. Asset; Local Government Expenditure; Internet Financial Reporting; Local Government Dependency.Abstrak. Penyajian laporan keuangan di internet merupakan wujud upaya transparansi bagi pemerintah daerah. Beberapa hasil penelitian-penelitian sebelumnya menunjukkan transparansi keuangan pemerintah daerah didorong oleh faktor financialnya. Penelitian ini bertujuan untuk menguji pengaruh faktor keuangan terhadap kualitas internet financial reporting (IFR) pada pemerintah daerah di Indonesia. Pada penelitian ini, IFR diukur menggunakan indeks kualitas IFR. Faktor keuangan yang diteliti mencakup likuiditas, leverage, service level solvency (SLS) berbasis nilai belanja, SLS berbasis aset, dan ketergantungan daerah. Sampel sebanyak 91 dan dianalisis menggunakan regresi berganda dengan tingkat signifikansi 5%. Hasil penelitian ini menunjukkan bahwa SLS berbasis belanja berpengaruh signifikan negatif dan SLS berbasis aset berpengaruh signifikan positif terhadap kualitas IFR. Â